Latéralisation Et Trouble Du Langage Chez L’enfant: Comprendre L’occurrence De La Dyslexie Et De La Dysgraphie À L’école Primaire - Thierry, Seka Yapi Arsène (European Scientific Journal, ESJ, 2017)
This study analyzes language impairment to children in Ivorian primary school. More specifically, the study looks at the difficulties of learning in reading and writing still called dyslexia and dysgraphia. The data collection instruments such as observation, interview and questionnaire are used in the process and the hypothesis formulated links learning difficulties with biological and cultural factors to children. The quantitative and qualitative methods used on the basis of an experimental approach allow us to conclude that dyslexia and dysgraphia are consecutive to the biological lateralization and cultural prejudices of society.